Avaliação de quimioterápicos, expressão gênica e quantificação de proteínas em carcinoma de cabeça e pescoço - Galbiatti-Dias, Ana Lívia Silva (2014)
Introduction: Antifolate chemotherapies such as methotrexate (MTX) and 5-fluorouracil (5-FU) act inhibiting enzymes involved in folate pathway. These enzymes are important to DNA synthesis and cell growth. Chemotherapy dose may alter these levels of expression of these genes encoding enzymes involved in folate pathway and to influence in the response to treatment. Objectives: To evaluate relationship between mRNA and protein expression levels expression of MTHFR, DHFR, TYMS and SLC19A1 folate metabolic genes in laryngeal and oral cancer cell lines treated with MTX and 5-FU antifolate chemotherapies, separately. Materials and methods: HEP-2 (laryngeal cancer) and HN13 (oral cancer) cell lines were treated with 0.25, 25.0, and 75 μM of MTX and 10 ng/ml, 50 ng/ml, and 100 ng/ml of 5-FU, separately, for 24 hours/37°C. Flow Cytometry, Real-time PCR and Western blotting techniques were performed to analyzing the level of apoptosis, quantification of mRNA and quantification of proteins of genes, respectively. ANOVA and Bonferroni's post hoc tests were utilized for statistical analysis. P<0.05 was considered significant. Results: The higher concentration of MTX chemotherapeutic was associated with increased expression of MTHFR, DHFR, TYMS and SLC19A1 genes in laryngeal cancer cell line (p <0.05) and increased expression of DHFR and SLC19A1 genes in oral cancer cell line (p <0.05). The lower dose was associated with decreased expression of SLC19A1 gene laryngeal cancer (p <0.05). The higher concentration of 5-FU chemotherapy was associated with increased expression of DHFR gene in laryngeal cancer cell line (p <0.05) and increased expression of DHFR and TYMS genes in oral cancer cell line (p <0.05). The lower dose of 5-FU was associated with decreased expression of SLC19A1 gene. Conclusion: Exposure to low and high-dose of chemotherapeutics in oral cancer cell line can modulate the level of expression of genes involved in folate metabolism in laryngeal and oral cancer cell line.